Temporal modulation transfer functions obtained using sinusoidal carriers with normally hearing and hearing-impaired listeners - Moore, B C; Glasberg, B R (The Journal of the Acoustical Society of America, 2001)
Temporal modulation transfer functions were obtained using sinusoidal carriers for four normally hearing subjects and three subjects with mild to moderate cochlear hearing loss. Carrier frequencies were 1000, 2000 and 5000 Hz, and modulation frequencies ranged from 10 to 640 Hz in one-octave steps. The normally hearing subjects were tested using levels of 30 and 80 dB SPL. For the higher level, modulation detection thresholds varied only slightly with modulation frequency for frequencies up to 80 Hz, but decreased for high modulation frequencies. The decrease can be attributed to the detection of spectral sidebands. For the lower level, thresholds varied little with modulation frequency for all three carrier frequencies. The absence of a decrease in the threshold for large modulation frequencies can be explained by the low sensation level of the spectral sidebands. The hearing-impaired subjects were tested at 80 dB SPL, except for two cases where the absolute threshold at the carrier frequency was greater than 70 dB SPL; in these cases a level of 90 dB was used. The results were consistent with the idea that spectral sidebands were less detectable for the hearing-impaired than for the normally hearing subjects. For the two lower carrier frequencies, there were no large decreases in threshold with increasing modulation frequency, and where decreases did occur, this happened only between 320 and 640 Hz. For the 5000-Hz carrier, thresholds were roughly constant for modulation frequencies from 10 to 80 or 160 Hz, and then increased monotonically, becoming unmeasurable at 640 Hz. The results for this carrier may reflect "pure" effects of temporal resolution, without any influence from the detection of spectral sidebands. The results suggest that temporal resolution for deterministic stimuli is similar for normally hearing and hearing-impaired listeners.